Current view on pelvic inflammatory diseases: a literature review - Yu E Dobrokhotova; K R Bondarenko; A S Dvornikov (IP Berlin A.V., 2016)
This review presents the current published data on the epidemiology, etiology, pathogenesis, diagnosis and treatment of pelvic inflammatory disease (PID). Medical and social consequences of PID associated with the negative impact on women's reproductive health, emphasize the need for early antimicrobial therapy aimed at eradication of all potential etiotropic agents of the inflammatory focus. In the article the comparative analysis of the advantages and some limitations of conventional therapeutic strategies designed for use in situations with PID on Russian territory, the United States and Europe. Given the ubiquity of fluoroquinolone antibiotic resistance, insufficient sensitivity to first-line antibiotics (doxycycline) in the individual agents (in particular, Mycoplasma genitalium) treating PID in the circuit along with II-III generation cephalosporin, metronidazole, and it is desirable to recommend inclusion of azithromycin as an antibacterial drug first selection.